2019
DOI: 10.1002/hbm.24720
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of Down's syndrome and Alzheimer's neuropathology on default mode connectivity

Abstract: Down's syndrome is a chromosomal disorder that invariably results in both intellectual disability and Alzheimer's disease neuropathology. However, only a limited number of studies to date have investigated intrinsic brain network organisation in people with Down's syndrome, none of which addressed the links between functional connectivity and Alzheimer's disease. In this cross‐sectional study, we employed 11C‐Pittsburgh Compound‐B (PiB) positron emission tomography in order to group participants with Down's sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 68 publications
(114 reference statements)
4
37
0
Order By: Relevance
“…The works of Jacola et al (2011Jacola et al ( , 2014 were especially consistent since they only found statistically significant effects in the Control > DS comparisons in all the areas studied. Inconsistent and irregular activation patterns, as we mentioned, can be seen in the remaining works (Vega et al, 2015;Wan et al, 2017;Wilson et al, 2019). The two works carried out with a resting-state approach (Anderson et al, 2015) showed less activation in the functional connectivity networks presented in the DS samples.…”
Section: Fmri Description and Main Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…The works of Jacola et al (2011Jacola et al ( , 2014 were especially consistent since they only found statistically significant effects in the Control > DS comparisons in all the areas studied. Inconsistent and irregular activation patterns, as we mentioned, can be seen in the remaining works (Vega et al, 2015;Wan et al, 2017;Wilson et al, 2019). The two works carried out with a resting-state approach (Anderson et al, 2015) showed less activation in the functional connectivity networks presented in the DS samples.…”
Section: Fmri Description and Main Resultsmentioning
confidence: 76%
“…It is a source of noise to consider in this type of work. Except for the work of Wilson et al (2019), this issue is not mentioned in the rest of the works. In this regard, the proposals of Ciric et al (2017) should be taken into account in all fMRI studies and with more intensity in high-movement populations such as persons with DS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroimaging contributes to these rising developments by providing biomarkers that could improve comorbid AD diagnosis, inform prognosis, aid in deep phenotyping, allow for risk stratification, and track therapeutic efficacy in future clinical trials for people with DS. Models of AD pathophysiology propose a sequential progression of brain changes that are reflected by neuroimaging abnormalities, beginning with an early increase in Aβ PET tracer binding, followed by a gradual progression of neurofibrillary tau tangles, deficits in cerebral glucose metabolism (i.e., [ 18 F]-fluorodeoxyglucose-PET (FDG-PET) and gray matter atrophy and white matter dysfunction as seen with structural T 1 -weighted MRI, resting-state connectivity differences ( 5 ) and diffusion imaging ( 6 ). Indeed, as we will summarize in the next section, these stereotypical AD biomarker changes have often been recapitulated in the small but growing number of neuroimaging studies in DS.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous works focused on DS, the connectivity of the DMN to other brain regions shows different profiles in contrast to healthy control groups. The main characteristics of the connectivity in DS are the increased positive networks identified (i.e., hyper-connectivity), even in regions that, in control groups, are negative, and the decreasing of anti-correlation [ 19 , 20 , 21 ]. These data can explain the altered brain functioning of DS, due to the fact that anti-correlation is necessary to organize and segregate networks in the healthy brain [ 22 ].…”
Section: Introductionmentioning
confidence: 99%